Analysis of Liquid Waste Processing in the Animal Skin Cracker (Krupuk Kulit) Industry (Case Study in Seganteng Sub-District) - Risma Indriana; Supardiono Supardiono; Lalu Muhammad Aby Dujana (Tinta Emas Publisher, 2026)
Household-scale food industries can contribute to local livelihoods but often generate wastewater that is difficult to manage when treatment facilities are limited. This study analyzed the quality of liquid waste produced by the animal skin cracker (krupuk kulit) industry in Seganteng Urban Village, Cakranegara District, Mataram City, and formulated feasible treatment strategies using a SWOT approach. Wastewater samples were examined for pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), oil and grease, ammonia (NH3-N), and total chromium (Cr). The results were compared with the relevant Indonesian effluent quality standard for leather-related wastewater parameters. The findings showed that pH (7.43), TSS (35.00 mg/L), and total chromium (<0.040 mg/L) complied with the standard, whereas BOD (72.50 mg/L), COD (482.0 mg/L), oil and grease (899 mg/L), and ammonia (5.805 mg/L) exceeded the allowable limits. The SWOT calculation produced X = -0.85 and Y = -1.05, placing the industry in Quadrant IV, which indicates a defensive strategy. Therefore, the recommended actions emphasize gradual improvement through operator awareness, basic source reduction, low-cost treatment units, and technical assistance from government, universities, and environmental stakeholders.